Challenges and opportunities from water under soft nanoconfinement - Mezzenga, Raffaele (Frontiers in Soft Matter, 2023)
Nanoconfined water differs significantly from bulk water and challenges our common understanding of liquid water in both its most fundamental features, as well as in many applied aspects which stem out from its peculiar behavior. This brief perspective pinpoints both challenges associated with the study of water under soft nanoconfinement as well as some opportunities which arise from it, and which would not be at reach with standard bulk water. A special focus is given to the strong nanoconfinement ( 1-10 nm) offered by inverse lipidic mesophases, viewed as a natural soft nanoconfinement environment for water.